Case report: Drainage tube penetrating anastomosis as a rare cause for long-term nonunion of esophagogastric anastomosis in neck - Huang, Yaochen; Fu, Xiangning; Fu, Shengling (Frontiers in Surgery, 2023)
Anastomotic leakage is a life-threatening complication for esophageal cancer patients who received McKeown esophagectomy. Cervical drainage tube penetrating anastomosis is a rare but noteworthy cause of long-term nonunion of esophagogastric anastomosis. Here we reported two cases of esophageal cancer patients who received McKeown esophagectomy. The first case acquired the anastomotic leakage on postoperative day (POD) 7, and lasted for 56 days. The cervical drainage tube was removed at POD 38, and the leakage healed in 25 days. The second case acquired the anastomotic leakage on POD 8 and lasted for 95 days. The cervical drainage tube was removed at POD 57, and the leakage healed in 46 days. The two cases demonstrated the duration-prolonging effect of drainage tube penetrating anastomosis, which should not be overlooked in clinical practice. We suggested paying attention to the duration of leakage, the drainage fluids amounts and characteristics, and the imaging manifestations to help diagnose. If the cervical drainage tube penetrated the anastomosis, the tube should be eliminated as soon.